From Useto Influence: Student evaluation of teaching and the professional development of academics in HigherEducation - Nsibande, Rejoice (Critical Studies in Teaching and Learning, 2023)
The literature raises concerns that Student Evaluation of Teaching (SET) is not always used effectively to transform teaching practice in higher education. This paper reports on a study that was conducted across four faculties of a research-intensive university in South Africa to examine 17 academics’ engagement in a self-driven SET process. Kirkhart’s integrated theory of evaluation influence was used to analyse the collected data. Findings indicate that participation in self-driven SET influenced the academics to reflect deeply on their approaches, to prioritise context specific challenges and to interrogate elicited feedback to better understand students and their own engagement with teaching and learning. I argue that the use of SET in evaluating performance, limits and underplays the importance of personal and  contextual  factors  that  are  crucial  to support effective practices. The paper suggests that to complement the unavoidable institutional standardised processes whilst ensuring effective SET, robust self-driven processes should be promoted.